Investigating corporate entrepreneurship strategy through digital transformation: a dynamic capabilities perspective - Hong Chen; Sujinda Popaitoon; Atthaphon Mumi (Journal of Innovation and Entrepreneurship)
Abstract From the perspective of dynamic capabilities, Corporate Entrepreneurship (CE) is regarded as a key mechanism driving corporate growth and sustainable competitiveness. However, in the digital era, how manufacturing enterprises can effectively activate their corporate entrepreneurial capabilities through Digital Transformation (DT) remains insufficiently explored. Based on Teece’s dynamic capabilities framework and utilizing panel data from 1070 A-share listed manufacturing companies in China, this study innovatively employs Python-based automation program to crawl and quantify the degree of digital transformation in manufacturing firms, empirically examining the impact of DT on corporate entrepreneurship strategy (CE strategy). The findings reveal that digital transformation significantly and positively promotes entrepreneurial activities in manufacturing enterprises. This effect demonstrates DT as an important pathway for constructing new dynamic capabilities and enabling CE strategy. Additionally, the findings reveal that the moderating effect of state ownership on the “DT-CE strategy” relationship is not significant overall. However, evidence of regional heterogeneity suggests that this relationship may vary depending on specific institutional and developmental contexts across regions. This study not only enriches digital entrepreneurship theory and mixed-ownership reform research but also deepens the understanding of how dynamic capabilities shape manufacturing enterprises’ sustainable competitiveness through digital transformation.